Effect of different surface treatments on microtensile bond strength of two types of composite substructures with ceramic by resin cements - Negin Tabari; Seyedkamal Seyedmajidi; Toloo Jafari; Soraya Khafri; Homayoon Alaghehmand (Babol University of Medical Sciences, 2021)
Introduction: The aim of this study was to investigate the effect of different surface treatments on the microtensile bond strength (µTBS) of two types of composite substructures with Vita Mark II ceramics by resin cement. Materials & Methods: Sixty-four substructure specimens were molded from two dual-cure composites Core.it and Build-it, equally, and cured by LED light. The specimens of each group were randomly divided into 4 subgroups (n=8) treated by one of HF acid 10%, air abrasion, Er: YAG laser, and one group without any treatment (control group), and then the specimens of each group were bonded to Vita Mark II CAD/CAM ceramic blocks using two Duo-Link and Panavia F 2.0 resin (n=4 and 20 slice in any group). Each final specimen was thermocycled between 5 °C and 55 °C for 2500 cycles and then cut by a slow speed saw to obtain 5 sticks with cross-section dimensions of about 1×1 mm². The µTBS test was done at a speed of 0.5 mm/min by Universal Testing Machine. The fracture pattern was then determined using a stereomicroscope. Statistical differences between groups were determined by one-way ANOVA using Tukeychr('39')s multiple comparison tests. Results: Among all 16 groups, the highest µTBS was observed in the group with Core.it substructure composite and Duo-link resin cement without any surface treatment and after that in the second step in build-it substructure composite group and Panavia resin cement without surface treatment. The most common fracture pattern in all groups was cohesive in resin cement (P value<0.05). Conclusion: According to this study, composite substructure surface treatment by hydrofloridric acid, laser and air abrasion reduced µTBS between substructure- ceramic and so  is not recommended.